2012
DOI: 10.1093/toxsci/kfs334
|View full text |Cite
|
Sign up to set email alerts
|

Acute and Subchronic Toxicity Evaluation of Poly(ɛ-Caprolactone) Lipid-Core Nanocapsules in Rats

Abstract: Owing to concerns over the effects of the physicochemical properties of nanoparticles and their interaction with biological systems, further investigation is required. We investigated, for the first time, the toxicity of lipid-core nanocapsules (LNCs) containing a polymeric wall of poly(ε-caprolactone) and a coating of polysorbate 80 used as drug delivery devices (~245nm) in Wistar rats after single- and repeated-dose treatments. The suspensions were prepared by interfacial deposition of the polymer and were p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 57 publications
3
34
1
1
Order By: Relevance
“…20,54 In vitro and in vivo studies reported that the large surface area of NPs results in a high reactivity, which could lead to cytotoxicity. 16,[20][21][22]54 The NPs' properties such as chemical composition, shape, size, surface chemistry, and large surface reactivity are mainly responsible for the possible toxicological effects caused by NPs. 16,21,22 Thus, although the present work did not explore different physical and chemical characteristics of nanocapsules, this alternative model is recommended for toxicological screening because it allows a systematic evaluation of many particularities of nanomaterials, yielding rapid and accurate results.…”
Section: Caenorhabditis Elegans As An Alternative In Vivo Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…20,54 In vitro and in vivo studies reported that the large surface area of NPs results in a high reactivity, which could lead to cytotoxicity. 16,[20][21][22]54 The NPs' properties such as chemical composition, shape, size, surface chemistry, and large surface reactivity are mainly responsible for the possible toxicological effects caused by NPs. 16,21,22 Thus, although the present work did not explore different physical and chemical characteristics of nanocapsules, this alternative model is recommended for toxicological screening because it allows a systematic evaluation of many particularities of nanomaterials, yielding rapid and accurate results.…”
Section: Caenorhabditis Elegans As An Alternative In Vivo Modelmentioning
confidence: 99%
“…Previous studies from our research group have evaluated acute and subchronic LNC toxicity in rats after intraperitoneal and intradermal administration, whose results showed the safety of this promising drug delivery system. [21][22][23] However, the great number of new nanomaterials requires the use of in vivo models to provide the toxicological screening, 24 and following the three Rs policy (to reduce, replace, and refine the animals used for this purpose) is important, 25 especially with alternative in vivo models.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, necropsy of the animals at the end of treatments showed agglomeration of LNC or AcE-LNC on the tissues of the abdominal cavity ( Figure S3B), which may contribute to the systemic toxic effects of ip injection. Indeed, Bulcão et al 67 showed similar peritoneal LNC accumulation in rats after local injection of LNC (72.12×10 12 LNC/kg). It may be surmised that the clearance systems in the peritoneal cavity, as lymph node draining and macrophages engulfment, are not sufficient to clear daily injections of LNCs.…”
Section: Ip or Oral Lnc Treatment Inhibits The Melanoma Developmentmentioning
confidence: 81%
“…Moreover, it is well demonstrated that the LNC formulation has no potential for either acute or sub-chronic toxicity in vivo. 32,33 The loading of MTX on LNC provides a stable pharmaceutical formulation with a high concentration in inflammatory sites.…”
Section: Discussionmentioning
confidence: 99%